The retirement guide : a comprehensive handbook on aging, retirement, caregiving and health : how to plan and pay for it - Midlam, Michael S. (Insomniac Press, 2004)
As you plan for the future, you'd best make this book your bible if you don't want to spend the latter years of your life toothless and frail, eating cat food from the can with your cable TV cut-off indefinitely. People over 65 years old constitute the fastest growing segment of the American population. Today, there are 35 million Americans over 65. By 2011, as the first baby boomers turn 65, 42 million people will be senior citizens. And by 2030, it is estimated that nearly one in four Americans will be over 65. The aging population will radically change society as individuals face the challe.